A study of service recovery of customer complaint at Telekom Malaysia Berhad ™ in Kota Bharu / Fatin Nadhirah Ahmad Shafien - Ahmad Shafien, Fatin Nadhirah (2014)
As we know, customers are important for all the business around the world because they are the biggest contributors for the company. Thus, the companies need to provide a good service recovery in order to keep the customer loyalty. The research has been undertaken to determine the factors influencing the service recovery of customer complaint at Telekom Malaysia in Kota Bharu. The objectives of this research are to determine the dominant factor that contributes to service recovery of customer’s complaint and to determine significant relationship between responsiveness, assurance and treat customers fairly with the service recovery of customer complaint. The study done by using the primary data as sources. Data were collected from 100 respondents in Kelantan who consume the Telekom’s services by using questionnaires. The results show that there is some positive relationship between the measurements taken with the service recovery of customer complaint at Telekom Malaysia in Kota Bharu. The result obtained from the correlation analysis revealed that all variables, responsiveness, assurance and treat customers fairly were related with the factors that contribute towards service recovery of customer complaint. Thus, all of the factors stated are relatively important and give contribution to the dependent variable. From the result that the researchers have gained, it stated that, responsiveness and assurance have significant relationship with dependent variable, service recovery of customer complaint. Besides, treat customers fairly has no significant relationship with the service recovery of customer complaint at Telekom Malaysia in Kota Bharu. To conclude, the responsiveness and assurance appeared to provide significant result with the service recovery of customer complaint